Atomic-scale catalyst for laser solid-phase synthesis as well as preparation method and application of atomic-scale catalyst

Through laser solid-phase synthesis method, the metal salt precursor is reduced by laser irradiation to form an atomic catalyst, which solves the problems of efficient, simple and batch production in the prior art, and achieves cost reduction and wide application.

CN119524838AActive Publication Date: 2025-02-28NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411791415.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The prior art is difficult to achieve efficient, simple and batch production of atomic catalysts, resulting in high production costs.

Method used

By using the laser solid phase synthesis method, a solid phase reaction system is formed, including a carbon-based material with multiple anchor points on the surface and a metal salt precursor supported on the carbon-based material, laser irradiation is performed to reduce the metal salt precursor to form an atomic catalyst.

Benefits of technology

It achieves simple process, strong universality and mass production, reduces the production cost of catalysts, and meets the needs of the chemical industry, petroleum processing industry, energy, pharmaceutical industry and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524838A_ABST
    Figure CN119524838A_ABST
Patent Text Reader

Abstract

The invention discloses an atomic-scale catalyst for laser solid-phase synthesis as well as a preparation method and application of the atomic-scale catalyst. The preparation method comprises the steps that a solid-phase reaction system is formed, the solid-phase reaction system comprises a carbon-based material with a plurality of anchoring points on the surface and a metal salt precursor loaded on the carbon-based material, and the metal salt precursor is combined with the anchoring points; and carrying out laser irradiation on the solid-phase reaction system, so that the metal salt precursor is reduced to form the atomic-scale catalyst. The atomic-scale catalysts prepared by the method are diversified and comprise monatomic catalysts, diatomic catalysts, monatomic alloys, diatomic alloys, atomic clusters and the like. The preparation method is simple in process, high in universality and suitable for various carbon-based materials containing anchoring points and metal elements with catalytic activity, atomic-scale catalysts can be produced in batches, and the requirements for various catalysts in the fields of chemical industry, petroleum processing industry, energy, pharmaceutical industry, environmental protection and the like can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a laser solid phase synthesis atomic-level catalyst and a preparation method and application thereof. Background Art

[0002] Catalysts play an important role in many industries such as chemical industry, medical treatment, agriculture and environmental protection. Hydrogen energy is a secondary clean energy with high calorific value. Catalysts are one of the most critical materials in the hydrogen production industry, but they still face two major bottlenecks in preparation and application. One is the lack of mass production methods in technology; the other is the huge amount of consumption, which leads to the current cost of hydrogen production by electrolysis of water in my country as high as 38 yuan / kg. In order to solve the above problems, atomic-level catalytic materials have developed rapidly. Atomic-level catalytic materials include single atoms, diatoms, atomic clusters, and single and diatomic alloys. They reduce the material cost by reducing the size of traditional nanoparticle catalysts to increase the atomic utilization of catalysts. When the catalyst size is reduced to the atomic level, the atomic utilization is maximized, and the strong interaction between metal and carrier can bring high stability. At present, the methods for efficiently and quickly obtaining atomic-level catalysts include carbon thermal shock method, rapid moving bed pyrolysis method, microwave heating method, and Joule rapid heating method, but these methods have specific requirements for carriers and are difficult to scale up production.

[0003] In terms of the preparation of atomic-level catalytic materials, patent documents CN112221528A and CN113430540A disclose methods for synthesizing single-atom catalysts using conventional hydrothermal methods. The preparation process requires a reactor, high-temperature hydrothermal and multi-step heating, which is not conducive to mass production. Pulsed laser liquid phase ablation technology was first proposed by Czech and German scientists in the 1990s and has unique advantages in the preparation and modification of functional nanomaterials. Patent document CN114029505A discloses a method for obtaining atomic-level catalysts using laser ablation of precursors in the liquid phase. The reaction process needs to rely on a specific liquid phase environment. Based on this, how to simply, efficiently, and mass-produce atomic-level catalysts is an urgent problem to be solved. Summary of the invention

[0004] The main purpose of the present invention is to provide a laser solid phase synthesis atomic level catalyst and its preparation method and application, so as to overcome the shortcomings of the prior art.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: One aspect of the present invention provides a method for preparing an atomic-level catalyst by laser solid-phase synthesis, which comprises: forming a solid-phase reaction system, the solid-phase reaction system comprising a carbon-based material having a plurality of anchoring points on the surface and a metal salt precursor loaded on the carbon-based material, the metal salt precursor being combined with the anchoring points; and subjecting the solid-phase reaction system to laser irradiation so that the metal salt precursor is reduced to form an atomic-level catalyst.

[0006] Another aspect of the present invention provides an atomic-level catalyst prepared by the above-mentioned preparation method. The atomic-level catalyst includes any one of a single-atom catalyst, a diatomic catalyst, a single-atom alloy catalyst, a diatomic alloy catalyst, and an atomic cluster catalyst.

[0007] Another aspect of the present invention provides use of the aforementioned atomic-scale catalyst in a catalytic reaction.

[0008] Furthermore, the application includes application in hydrogen production, oxygen production, industrial organic energy production, energy conversion, medical treatment, agriculture or environmental protection.

[0009] Compared with the prior art, the present invention has at least the following beneficial effects: (1) Simple process: In the present invention, photothermal / photochemical reaction occurs the moment the laser spot contacts the carrier material, reducing the metal salt precursor loaded on the carrier, and efficiently preparing atomic-level dispersed materials; (2) Strong universality: The synthesis method of the present invention does not rely on a specific reaction environment and is applicable to various carbon-based materials containing anchor points and metal elements with catalytic activity. It can design and select materials for the active centers required for catalytic reactions and prepare atomic-level catalysts; (3) Mass production: The synthesis parameters are stable during the laser solid-phase synthesis process. By regulating the laser parameters, atomic-level catalysts can be mass-produced to meet the needs of various catalysts in the chemical industry, petroleum processing industry, energy, pharmaceutical industry and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0011] Figure 1 is an electron microscope image of the Pt single atom catalyst prepared in Example 1 of the present invention; Figure 2a is an electron microscope image of the Fe single atom catalyst prepared in Example 4 of the present invention; Figure 2b This is the stability test result of the Fe single atom catalyst prepared in Example 4 of the present invention used in a zinc-air battery; Figure 3 is an electron microscope image of the Co single atom catalyst prepared in Example 8 of the present invention; Figure 4 is an electron microscope image of the Ni single atom catalyst prepared in Example 10 of the present invention; Figure 5a is a spherical aberration electron microscope image of the Pt1Co single-atom alloy catalyst particles prepared in Example 16 of the present invention; Figure 5b is a spherical aberration electron microscope image of the (PtRu)1Co diatomic alloy catalyst particles prepared in Example 25 of the present invention; Figure 5c This is the chronovoltaic curve of the (PtRu)1Co diatomic alloy catalyst prepared in Example 25 of the present invention in the hydrogen evolution reaction. DETAILED DESCRIPTION

[0012] In view of the problems existing in the above-mentioned prior art, the inventors of the present invention have conducted extensive and in-depth research and have provided a laser solid-phase synthesis of atomic-level catalysts and a preparation method and application thereof. The laser solid-phase synthesis of atomic-level catalysts mainly adopts a one-step laser irradiation to load a carbon carrier with a metal salt precursor. The carbon carrier is a carbon-based material containing sufficient anchor points, and the atomic-level catalyst is directly obtained. The synthesis method is simple and efficient, does not require special equipment and a high temperature and high pressure environment, and can be mass-produced.

[0013] The technical solution, its implementation process and principle will be further explained as follows.

[0014] As one aspect of the technical solution of the present invention, a method for preparing an atomic-level catalyst by laser solid-phase synthesis is provided, comprising: forming a solid-phase reaction system, the solid-phase reaction system comprising a carbon-based material having a plurality of anchoring points on the surface and a metal salt precursor loaded on the carbon-based material, the metal salt precursor being combined with the anchoring points; and subjecting the solid-phase reaction system to laser irradiation so that the metal salt precursor is reduced to form an atomic-level catalyst.

[0015] In some embodiments, the formation process of the solid phase reaction system specifically includes: contacting or mixing a liquid phase system containing a metal salt precursor with the carbon-based material; and removing the solvent in the liquid phase system to obtain the solid phase reaction system.

[0016] Furthermore, the carbon-based material is used as a filter material to filter the liquid phase system to form the solid phase reaction system.

[0017] Furthermore, the carbon-based material is dispersed in the liquid phase system and dried to form a film to form the solid phase reaction system.

[0018] Furthermore, the carbon-based material and the liquid phase system are both dissolved in an organic solvent and freeze-dried to form the solid phase reaction system.

[0019] In the present invention, the anchor points on the carbon-based material are chemically bonded to the metal atoms in the metal salt precursor. The metal salt precursor is randomly distributed on the carbon-based material before laser irradiation. During the laser irradiation process, the metal salt is reduced to a single atom and bonded to the anchor points. The anchor points are bonded to the metal atoms, fixing the metal atoms at these positions. These metal atoms are stabilized at the anchor points during subsequent laser irradiation, ultrasound, and electrochemical testing. In addition, the process of rapid heating and cooling of the laser irradiated precursor will retain a large number of anchor points, and the number of anchor points is sufficient.

[0020] In some embodiments, for graphene oxide carriers, the precursors after uniform liquid phase mixing are freeze-dried and the precursor ions are dispersed on negatively charged graphene oxide sheets; then, after laser irradiation, the graphene oxide is reduced and a large number of oxygen-containing functional groups are retained on the surface, which can anchor metal atoms. For ZIF carriers, a large number of N atoms retained on the surface of the carbonized material can anchor metal atoms.

[0021] In some embodiments, in the solid phase reaction system, the mass ratio of the carbon-based material to the metal salt precursor is in the range of 20:1 to 50:1.

[0022] In some embodiments, the mass fraction of the metal salt precursor in the liquid system is 30% to 70%.

[0023] In some embodiments, the wavelength of the laser is in the range of 248 nm to 10.6 μm.

[0024] In some embodiments, the scanning speed of the laser is 500 to 2000 mm / s.

[0025] In some embodiments, the power of the laser is 0.5 ~200 W.

[0026] In some embodiments, the frequency of the laser is 1 to 1000 kHz.

[0027] In some embodiments, the spot diameter of the laser is 20 μm~1 cm.

[0028] In some embodiments, the pulse width of the laser is 10 ps to 10 ms.

[0029] In some embodiments, the irradiation time is 10 to 60 min, wherein the laser irradiation time is related to the amount of the carrier of the carbon-based material.

[0030] In some embodiments, the type of laser includes any one of an excimer laser, a fiber laser, a carbon dioxide laser, a solid-state laser, etc., but is not limited thereto.

[0031] In some embodiments, the metal element in the metal salt precursor includes any one or a combination of two or more of copper, nickel, iron, cobalt, palladium, platinum, ruthenium, iridium, titanium, manganese, chromium, etc., but is not limited thereto.

[0032] In some embodiments, the carbon-based material containing anchor points includes any one of carbon-based materials containing non-metallic elements, carbon-based materials containing material defects, etc., but is not limited thereto. These anchor points can be formed on the carbon-based material by chemical methods. The non-metallic elements include any one or a combination of two or more of N, O, S, P elements, etc., but are not limited thereto. The material defects include any one of vacancies, interstitial atoms, substitutional atoms, etc., but are not limited thereto.

[0033] In some embodiments, the carbon-based material includes any one or a combination of carbon-nitrogen materials that do not require carbonization, carbon nanotube materials, etc., but is not limited thereto. The carbon-nitrogen material includes any one of g-C3N4, C3N2, C2N, CN, etc., but is not limited thereto.

[0034] In some embodiments, the carbon-based material further comprises any one or a combination of two or more of graphene oxide, metal organic framework material, and natural wood to be carbonized, but is not limited thereto. The carbonization method comprises any one of tube furnace heating, microwave heating, laser heating, etc., but is not limited thereto.

[0035] In some typical embodiments, the preparation method of laser solid phase synthesis single / double atom alloy catalyst specifically comprises the following steps: (1) Mixing metal organic framework ZIF-67, polybenzimidazole PBI and dimethylacetamide DMAC, and stirring to obtain solution A; coating solution A on a glass plate, soaking it in deionized water, and drying it; irradiating the material on the glass plate with a laser, and collecting powder A; (2) uniformly mixing the metal salt precursor and DMAC to obtain solution B; (3) Mix powder A, solution B and polybenzimidazole PBI, and stir evenly to obtain solution C; (4) Apply solution C onto the support, soak it in deionized water, and then take it out and dry it; (5) After irradiating the material on the support with laser, powder B is collected.

[0036] Among them, DMAC is in liquid phase when used as solvent. After being immersed in water, water will replace DMAC solvent and promote PBI to form a solid porous organic skeleton. Similarly, a fully aromatic polyamide obtained by the polycondensation reaction of DADS and CBSI can form a film under NMP dissolution and form a solid porous organic skeleton under the action of water.

[0037] Furthermore, the concentration of ZIF-67 in the solution in step (1) is 10-30 g / L.

[0038] Furthermore, in step (1), the mass concentration of polybenzimidazole in solution A is 10-30%.

[0039] Furthermore, the thickness of the coating on the glass plate in step (1) is 20-100 μm.

[0040] Furthermore, in step (2), the concentration of the metal salt precursor in solution B is 0.001-0.2 M.

[0041] Furthermore, in step (3), the concentration of powder A in solution C is 10-30 g / L.

[0042] Furthermore, steps (1)-(3) are combined into one step: the metal organic framework ZIF-67, the metal salt precursor, the polybenzimidazole PBI and the dimethylacetamide DMAC are mixed and stirred to obtain a solution C.

[0043] Furthermore, the mass ratio of the metal organic framework ZIF-67, the metal salt precursor, the polybenzimidazole PBI and the dimethylacetamide DMAC ranges from 10:1:1:1 to 10:3:3:3.

[0044] Furthermore, in step (5), the support is any one of a quartz glass plate, a nickel mesh, a carbon paper, a carbon felt and a carbon cloth, but is not limited thereto.

[0045] In some typical embodiments, the method for preparing a single-atom catalyst by laser solid phase synthesis specifically comprises the following steps: (1) ZIF-8 and NaCl were mixed and ground, and then carbonized in a tube furnace to obtain powder A; (2) Mixing powder A, a metal salt precursor, and methanol and stirring them uniformly to obtain solution A; (3) vacuum filtering solution A through a filter onto a PTFE membrane and drying; (4) After irradiating the material on the PTFE membrane with laser, powder B is collected.

[0046] Furthermore, in step (1), the mass ratio of ZIF-8 to NaCl is in the range of 1:2 to 2:1.

[0047] Furthermore, the grinding time in step (1) is 10 to 50 min.

[0048] Furthermore, in step (2), the mass ratio of powder A to metal salt precursor and methanol is in the range of 2:1 to 1:1.

[0049] In some embodiments, the metal salt precursor provides a metal element capable of forming a catalytically active metal element, which can form a catalytically active metal element including any one of copper, nickel, iron, cobalt, palladium, platinum, ruthenium, iridium, titanium, manganese, and chromium, but is not limited thereto.

[0050] The laser solid-phase synthesis atomic-level catalyst method proposed in the present invention can instantly reduce the metal salt precursor through laser radiation to produce a large number of single atoms, diatomic atoms, single-atom alloys, diatomic alloys and atomic clusters loaded on the surface of a carbon-based carrier. The types of metal elements are diverse and the preparation method is innovative.

[0051] In addition, laser irradiation during the laser reduction of metal salts and the carbonization of uncarbonized carriers will not change the characteristics of the anchoring points. An anchored atomic-level catalyst material is directly formed after laser irradiation, and has good stability.

[0052] As another aspect of the technical solution of the present invention, an atomic-level catalyst prepared by the above-mentioned preparation method is provided. The atomic-level catalyst includes any one of a single-atom catalyst, a diatomic catalyst, a single-atom alloy catalyst, a diatomic alloy catalyst, and an atomic cluster catalyst.

[0053] As another aspect of the technical solution of the present invention, it also provides the use of the aforementioned atomic-level catalyst in a catalytic reaction.

[0054] Furthermore, the application includes application in hydrogen production, oxygen production, industrial organic energy production, energy conversion, medical treatment, agriculture or environmental protection.

[0055] The atomic-level catalyst involved in the present invention can accelerate a variety of catalytic reactions, which is beneficial to the production of hydrogen, oxygen and a variety of industrial organic energy products. It has shown significant advantages in the field of energy conversion and has shown a trend of replacing traditional products in many industries such as medicine, agriculture and environmental protection.

[0056] In summary, the present invention provides a method for preparing an atomic-level catalyst by laser solid-phase synthesis, which directly obtains an atomic-level catalyst by one-step laser irradiation of a carbon carrier loaded with a metal salt precursor. The synthesis method is simple and efficient, does not require special equipment and a high-temperature and high-pressure environment, can be mass-produced, and can meet the needs of various catalysts in the fields of chemical industry, petroleum processing industry, energy, pharmaceutical industry, and environmental protection.

[0057] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with Examples and Comparative Examples. It should be understood that the specific embodiments and comparative examples described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art will make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention, without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0058] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0059] Example 1 A method for laser solid phase synthesis of Pt single atom catalyst, the specific steps of which are as follows: (1) First, add 4 mL of 7 mg mL -1 The graphene oxide aqueous dispersion was filtered through a 0.2 μm pore size polytetrafluoroethylene filter membrane and freeze-dried; (2) Add 2 mL of 1 mmol L -1 The H2PtCl6 metal precursor solution passed through the polytetrafluoroethylene membrane containing graphene oxide and then freeze-dried to obtain a Pt precursor-graphene film. The mass ratio of the carbon-based material to the metal precursor was 35:1. During the freeze-drying process, solid ice directly sublimated into water vapor, [PtCl6] 2- The anionic complex is dispersed on the negatively charged graphene oxide sheets, and the oxygen-containing functional groups on the graphene serve as anchoring points.

[0060] (3) Using a solid-state laser, an infrared laser with a wavelength of 1064 nm, a pulse width of 5 ns, a repetition rate of 30 kHz and an average power of 3-10 W is focused to a spot size of about 1 mm and then irradiated once at a scanning speed of 1000 mm / s. During the laser irradiation process, the graphene oxide is simultaneously reduced, retaining a large number of oxygen-containing functional groups, which serve as anchor points to form chemical bonds with the Pt atoms formed by the laser reduction of the metal salt, thereby obtaining a Pt single-atom catalyst.

[0061] Figure 1 This is an electron microscope image of the Pt single atom catalyst prepared in Example 1 of the present invention.

[0062] Example 2 The difference between this example and Example 1 is that in this example, 4 mL of 7 mg mL -1 The graphene oxide aqueous dispersion was replaced with 4 mL of 4.1 mg mL -1Graphene oxide aqueous dispersion to obtain Pt atomic cluster catalyst.

[0063] Example 3 The difference between this example and Example 1 is that in this example, 4 mL of 7 mg mL -1 The graphene oxide aqueous dispersion was replaced with 4 mL of 10 mg mL -1 Graphene oxide aqueous dispersion.

[0064] However, through comparison, it is found that the present embodiment can also obtain a Pt single atom catalyst, but the Pt single atom concentration in the Pt single atom catalyst of Example 1 is higher.

[0065] Example 4 A method for laser solid phase synthesis of Fe single atom catalyst, the specific steps of which are as follows: (1) First, 10 mmol Zn(NO3)2·6H2O was dissolved in 100 mL methanol solution and 50 mmol 2-methylimidazole was dissolved in 100 mL methanol solution to form a solution, which was mixed and stirred. After 24 hours, the precipitate was washed several times by centrifugation, and ZIF-8 was collected after drying at 60 °C overnight. (2) 2.0 g of ZIF-8 was gently ground with a motor and pestle and mixed with 2.0 g of NaCl for 10 min, and then carbonized by pyrolysis at 1000 °C under flowing Ar gas for 2 h. Finally, porous carbon was obtained by washing with deionized water three times to remove NaCl and drying at 60 °C for 12 h. The porous carbon contained a large amount of N elements, which served as anchor points.

[0066] (3) Add 200 mg of porous carbon and 10 mg of FeCl3·6H2O powder to 100 mL of methanol, stir constantly at room temperature for 12 hours, and freeze-dry to obtain Fe 3+ -porous carbon precursor and coated on a glass plate, the mass ratio of carbon-based material to metal precursor is 20:1.

[0067] (4) A pulsed laser with a wavelength of 355 nm, a power of 3 W, and a spot size of 0.45 mm was used with a power of 50 mJ cm −2 The laser energy density, pulse repetition rate of 20 kHz, pulse duration of 8 ns, scanning rate of 500 mm / s and scanning distance of 0.01 mm were used to ablate Fe. 3+ -porous carbon precursor, to obtain Fe single atom dispersed material, wherein the chemical bond formed between Fe and the anchor point can be represented by Fe-N4.

[0068] Figure 2a is an electron microscope image of the Fe single atom catalyst prepared in Example 4 of the present invention, Figure 2bThe stability test results of the Fe single-atom catalyst prepared in Example 4 of the present invention used in zinc-air batteries show that the single-atom catalyst has better stability than the commercial catalyst.

[0069] Example 5 The difference between this embodiment and embodiment 4 is that in this embodiment, 10 mg FeCl3·6H2O is increased to 50 mgFeCl3·6H2O to obtain a Fe atomic cluster catalyst, and the rest is implemented in the same manner as embodiment 4.

[0070] Example 6 The difference between this embodiment and embodiment 4 is that in this embodiment, 200 mg of porous carbon is replaced by 350 mg of porous carbon.

[0071] Example 7 The difference between this embodiment and embodiment 4 is that in this embodiment, 200 mg of porous carbon is replaced by 500 mg of porous carbon.

[0072] However, through comparison, it is found that Examples 6 and 7 can also obtain Fe single atom catalysts, but the Fe single atom concentration in the Fe single atom catalyst of Example 4 is higher.

[0073] Example 8 The difference between this embodiment and embodiment 4 is that 10 mg of FeCl3·6H2O powder is replaced by 10 mg of CoCl3·6H2O powder to obtain a Co single atom catalyst, and the rest is the same as embodiment 4.

[0074] Figure 3 This is an electron microscope image of the Co single atom catalyst prepared in Example 8 of the present invention.

[0075] Example 9 The difference between this embodiment and embodiment 4 is that 10 mg of FeCl3·6H2O powder is replaced by 50 mg of CoCl3·6H2O powder to obtain a Co atomic cluster catalyst, and the rest is the same as embodiment 4.

[0076] Example 10 The difference between this embodiment and embodiment 4 is that 10 mg of FeCl3·6H2O powder is used to replace 10 mg of NiCl3·6H2O powder to obtain a Ni single atom catalyst, and the rest is the same as embodiment 4.

[0077] Figure 4 This is an electron microscope image of the Ni single atom catalyst prepared in Example 10 of the present invention.

[0078] Embodiment 11 The difference between this embodiment and embodiment 4 is that 10 mg of FeCl3·6H2O powder is replaced by 50 mg of NiCl3·6H2O powder to obtain a Ni atomic cluster catalyst, and the rest is the same as embodiment 4.

[0079] Example 12 A method for laser solid phase synthesis of S and N coordinated carbon-based Pt single atom catalysts, the specific steps of which are as follows: (1) First, 10 mmol Zn (NO3)2·6H2O was dissolved in 100 mL methanol solution and 50 mmol 2-methylimidazole was dissolved in 100 mL methanol solution to form a solution, mixed and stirred, and the precipitate was washed several times by centrifugation after 24 hours. After drying at 60 °C overnight, the white powder ZIF-8 was collected; (2) Mix 50 mg of metal organic framework ZIF-8, 0.5 mL of 15% PBI, 12 mg of thiourea, and 0.2 mL of 20 mmol / L Pt precursor solution, and stir to obtain a precursor solution; (3) Use a coater to apply 1.5 mL of the precursor solution onto a quartz glass plate with a thickness of 60 μm, soak it in deionized water for 2 h, and then take it out and dry it; (4) Excimer ultraviolet laser was used to irradiate the precursor material on the quartz glass plate to obtain S and N coordinated carbon-based Pt single atom dispersed material. The mass ratio of carbon-based material to metal precursor was 25:1. The laser wavelength was 355 nm, the spot size was 20 μm, the repetition frequency was 1000 kHz, the power was 2 W, and the scanning speed was 500 mm / s.

[0080] Example 13 The only difference between this embodiment and embodiment 12 is that the thiourea in embodiment 12 is replaced by potassium dihydrogen phosphate to obtain a laser solid phase synthesized P, N coordinated carbon-based Pt single atom catalyst, and the rest is implemented in the same way as embodiment 12.

[0081] Embodiment 14 The difference between this example and Example 12 is that in this example, 0.2 ml of 20 mmol / L Pt precursor is increased to 0.3 ml of 20 mmol / L Pt precursor to obtain S, N coordinated Pt atomic cluster catalyst.

[0082] Embodiment 15 The difference between this example and Example 12 is that in this example, 0.2 ml of 20 mmol / L Pt precursor is replaced by 0.1 ml of 20 mmol / L Pt precursor.

[0083] However, through comparison, it was found that this embodiment can also obtain S and N coordinated carbon-based Pt single atoms, but the Pt single atom concentration in the Pt single atom catalyst of Example 12 is higher.

[0084] Example 16 A method for laser solid phase synthesis of Pt1Co single atom alloy catalyst particles, the specific steps of which are as follows: (1) First, 10 mmol Co (NO3)2·6H2O was dissolved in 100 mL of methanol solution and 50 mmol 2-methylimidazole was dissolved in 100 mL of methanol solution to form a solution, mixed and stirred, and the precipitate was washed several times by centrifugation after 24 hours. ZIF-67 was collected after drying at 60 °C overnight; (2) Mix 50 mg of metal organic framework ZIF-67, 0.3 mL of 15% PBI and 1.5 mL of dimethylacetamide (DMAC), and stir evenly to obtain a precursor solution; (3) Use a coater to apply 1.5 mL of the precursor solution onto a quartz glass plate with a thickness of 60 μm, soak it in deionized water for 2 h, and then take it out and dry it; (4) After irradiating the precursor on the glass plate with laser, the Co precursor loaded on the porous carbon is reduced to Co atoms, and ultra-small Co nanoparticles loaded on the porous carbon are collected as the substrate material, wherein the laser wavelength is 1064 nm, the spot size is 20 μm, the repetition frequency is 20 kHz, the power is 50 W, and the scanning speed is 2000 mm / s; (6) Mix 80 mg of porous carbon-supported ultrasmall Co nanoparticles, 0.5 mL of 20 mmol / L chloroplatinic acid, 2 mL of DMAC, and 0.3 mL of 15% polybenzimidazole (PBI); (7) Repeat step (3); (8) After irradiating the material on the glass plate with ultraviolet laser, the powder was collected to obtain a Pt1Co single-atom alloy catalyst. The mass ratio of carbon-based material to metal precursor was 20:1, the laser wavelength was 355 nm, the spot size was 20 μm, the repetition frequency was 1000 kHz, the power was 2 W, and the scanning speed was 500 mm / s.

[0085] Figure 5a This is a spherical aberration electron microscope image of the Pt1Co single-atom alloy catalyst particles prepared in Example 16 of the present invention.

[0086] Embodiment 17 The difference between this example and Example 16 is that in this example, 0.5 mL 20 mmol / L chloropalladic acid is used instead of 0.5 mL 20 mmol / L chloroplatinic acid to obtain the Pd1Co single atom alloy.

[0087] Embodiment 18 The difference between this example and Example 16 is that in this example, 0.5 mL 20 mmol / L chlororuthenic acid is used instead of 0.5 mL 20 mmol / L chloroplatinic acid to obtain Ru1Co single atom alloy.

[0088] Embodiment 19 The difference between this example and Example 16 is that in this example, 0.5 mL 20 mmol / L chloroiridic acid is used instead of 0.5 mL 20 mmol / L chloroplatinic acid to obtain the Ir1Co single atom alloy.

[0089] Embodiment 20 The difference between this example and Example 16 is that in this example, 0.5 mL 20 mmol / L titanium tetrachloride is used instead of 0.5 mL 20 mmol / L chloroplatinic acid to obtain Ti1Co single atom alloy.

[0090] Embodiment 21 The difference between this example and Example 16 is that in this example, 0.5 mL of 20 mmol / L manganese chloride tetrahydrate is used instead of 0.5 mL of 20 mmol / L chloroplatinic acid to obtain a Mn1Co single-atom alloy.

[0091] Embodiment 22 The difference between this embodiment and embodiment 16 is that in this embodiment, 0.5 mL 20 mmol / L chromium trichloride is used instead of 0.5 mL 20 mmol / L chloroplatinic acid to obtain Cr1Co single atom alloy.

[0092] Embodiment 23 The difference between this example and Example 16 is that in this example, 0.5 mL 20 mmol / L chloroplatinic acid is replaced with 0.35 mL 20 mmol / L chloroplatinic acid.

[0093] Embodiment 24 The difference between this example and Example 16 is that in this example, 0.5 mL 20 mmol / L chloroplatinic acid is replaced with 0.2 mL 20 mmol / L chloroplatinic acid.

[0094] However, through comparison, it was found that Examples 23 and 24 can also obtain Pt1Co single atom alloy catalysts, but the Pt1Co single atom concentration in the Pt1Co single atom alloy catalyst of Example 16 is higher.

[0095] Embodiment 25 A method for laser solid phase synthesis of (PtRu)1Co diatomic alloy catalyst particles, the specific steps of which are as follows: (1) First, 10 mmol Co (NO3)2·6H2O was dissolved in 100 mL methanol solution and 50 mmol 2-methylimidazole was dissolved in 100 mL methanol solution to form a solution, which was mixed and stirred. After 24 hours, the precipitate was centrifuged and washed several times. After drying at 60 °C overnight, the purple powder metal organic framework ZIF-67 was collected; (2) Mix 50 mg of the metal organic framework ZIF-67, 0.2 mL of 20 mmol / L chloroplatinic acid in DMAC solution, 1 mL of 20 mmol / L DMAC solution containing ammonium chlororuthenate, and 0.3 mL of 15% PBI and dimethylacetamide DMAC, and stir well to obtain solution A.

[0096] (3) Use an applicator to apply 1.5 mL of solution A on a quartz glass plate with a thickness of 60 μm, soak it in deionized water for 2 h, and then take it out and dry it; (4) After irradiating the material on the support with an ultraviolet laser, the powder was collected to obtain a (PtRu)1Co diatomic alloy catalyst. The mass ratio of the carbon-based material to the metal precursor was 25:1. The laser wavelength was 355 nm, the pulse width was 16 ps, the spot size was 20 μm, the repetition frequency was 1000 kHz, the power was 2 W, and the scanning speed was 500 mm / s.

[0097] Figure 5b This is a spherical aberration electron microscope image of the (PtRu)1Co diatomic alloy catalyst particles prepared in Example 25 of the present invention. Figure 5c The chronovoltaic curve of the (PtRu)1Co diatomic alloy catalyst prepared by the present invention in the hydrogen evolution reaction shows better stability than the commercial Pt / C catalyst.

[0098] Embodiment 26 The only difference between this embodiment and embodiment 25 is that the laser irradiation parameters used in this embodiment when preparing (PtRu)1Co diatomic alloy nanoparticles are: laser wavelength 532 nm, pulse width 10 ns, repetition frequency 100 kHz, power 200 W, and scanning speed 1000 mm / s.

[0099] Embodiment 27 The only difference between this embodiment and Embodiment 25 is that the laser irradiation parameters used in this embodiment when preparing (PtRu)1Co diatomic alloy nanoparticles are: laser wavelength 1064 nm, pulse width 10 ns, repetition frequency 100 kHz, power 125 W, and scanning speed 1000 mm / s.

[0100] Examples 26 and 27 can also form (PtRu)1Co diatomic alloy nanoparticles, but by comparison, it is found that the (PtRu)1Co diatomic alloy nanoparticles formed in Example 25 are smaller in size and more evenly distributed.

[0101] Embodiment 28 The difference between this embodiment and embodiment 25 is that the laser irradiation parameters used in this embodiment when preparing (PtRu)1Co diatomic alloy nanoparticles are: laser wavelength of 248 nm, spot size of 1 cm, repetition frequency of 0.1 kHz, power of 0.5 W, and scanning speed of 500 mm / s.

[0102] This embodiment can also form (PtRu)1Co diatomic alloy nanoparticles, but through comparison, it is found that the yield of (PtRu)1Co diatomic alloy nanoparticles formed in Example 25 is higher.

[0103] Embodiment 29 The difference between this example and Example 25 is that in this example, 0.2 ml of 20 mmol / L Pt precursor is replaced with 0.1 ml of 20 mmol / L Pt precursor.

[0104] However, through comparison, it was found that this embodiment can also obtain (PtRu)1Co diatomic alloy nanoparticles, but the concentration of Pt and Ru atoms in the (PtRu)1Co diatomic alloy nanoparticles of Example 25 is higher.

[0105] Embodiment 30 The difference between this example and Example 25 is that in this example, 0.2 ml of 20 mmol / L Pt precursor is replaced with 0.3 ml of 20 mmol / L Pt precursor.

[0106] However, by comparison, it is found that the present embodiment can also obtain (PtRu)1Co diatomic alloy nanoparticles, but PtRuCo alloy nanoparticles also exist.

[0107] Comparative Example 1 This comparative example is substantially the same as Example 1, except that: The pulsed laser irradiation was replaced by continuous infrared lamp irradiation, whose average power was consistent with the pulsed laser irradiation.

[0108] Since the reduction temperature of the precursor cannot be reached, single atom catalysts and atomic alloy catalysts cannot be formed in the end.

[0109] Comparative Example 2 This comparative example is substantially the same as Example 1, except that: The pulsed laser irradiation is replaced by transient pulse electric heating of the graphene film layer formed after filtration and drying, with the power kept consistent. Compared with the microsecond cooling rate of the former, the cooling rate of the latter is in the millisecond level. Longer temperature maintenance is firstly not conducive to the retention of functional groups, i.e., atomic anchoring points, and secondly, it is easy to cause atomic migration and agglomeration into nanoparticles.

[0110] Comparative Example 3 This comparative example is substantially the same as Example 1, except that: Graphene oxide is replaced by porous activated carbon with almost no active groups on the surface. Due to the lack of functional groups, the latter cannot provide a large number of single-atom anchoring points and lacks uniformly distributed single atoms. Further increasing the content of metal salt precursors can easily generate nanoparticles.

[0111] Comparative Example 4 This comparative example is substantially the same as Example 4, except that: Replacing the metal-organic framework ZIF-8 with porous activated carbon will also result in the loss of functional groups, i.e., atomic anchoring sites, and ultimately low single-atom loading.

[0112] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0113] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0114] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made and that elements of the described embodiments may be substituted with substantial equivalents without departing from the spirit and scope of the present invention. In addition, many modifications may be made to adapt a particular situation or material to the teachings of the present invention without departing from the scope of the present invention. Therefore, it is not intended herein to limit the present invention to the specific disclosed embodiments for carrying out the present invention, but rather it is intended that the present invention will include all embodiments within the scope of the appended claims.

Claims

1. A method for preparing an atomic-level catalyst by laser solid phase synthesis, characterized in that: include: forming a solid phase reaction system, the solid phase reaction system comprising a carbon-based material having a plurality of anchoring points on the surface and a metal salt precursor supported on the carbon-based material, the metal salt precursor being combined with the anchoring points; The solid phase reaction system is subjected to laser irradiation to reduce the metal salt precursor to form an atomic-level catalyst.

2. The preparation method according to claim 1, characterized in that: The formation process of the solid phase reaction system specifically includes: contacting or mixing a liquid phase system containing a metal salt precursor with the carbon-based material; and removing the solvent in the liquid phase system to obtain the solid phase reaction system.

3. The preparation method according to claim 2, characterized in that: Using the carbon-based material as a filter material to filter the liquid phase system to form the solid phase reaction system; Alternatively, the carbon-based material is dispersed in the liquid phase system and dried to form a film to form the solid phase reaction system; Alternatively, the carbon-based material and the liquid phase system are both dissolved in an organic solvent and freeze-dried to form the solid phase reaction system.

4. The preparation method according to claim 2, characterized in that: In the solid phase reaction system, the mass ratio of the carbon-based material to the metal salt precursor is in the range of 20:1 to 50:1; And / or, the mass fraction of the metal salt precursor in the liquid phase system is 30% to 70%.

5. The preparation method according to claim 1, characterized in that: The wavelength range of the laser is 248 nm~10.6 μm; And / or, the scanning speed of the laser is 500-2000 mm / s; And / or, the power of the laser is 0.5~200 W; And / or, the frequency of the laser is 1 to 1000 kHz; And / or, the spot diameter of the laser is 20 μm~1 cm; And / or, the pulse width of the laser is 10 ps to 10 ms; And / or, the irradiation time is 10 to 60 min; And / or, the laser involved in the laser includes any one of an excimer laser, a fiber laser, a carbon dioxide laser, and a solid laser.

6. The preparation method according to claim 1, characterized in that: The metal element in the metal salt precursor includes any one or a combination of two or more of copper, nickel, iron, cobalt, palladium, platinum, ruthenium, iridium, titanium, manganese and chromium.

7. The preparation method according to claim 1, characterized in that: The carbon-based material includes any one of a carbon-based material containing non-metallic elements and a carbon-based material containing material defects; the non-metallic elements include any one of N, O, S, and P elements or a combination of two or more thereof; the material defects include any one of vacancies, interstitial atoms, and substitutional atoms.

8. The preparation method according to claim 1 or 7, characterized in that: The carbon-based material includes any one of a carbon-nitrogen material that does not require carbonization and a carbon nanotube material, or a combination of two or more thereof; the carbon-nitrogen material includes any one of g-C3N4, C3N2, C2N, and CN; And / or, the carbon-based material also includes any one or a combination of two or more of graphene oxide, metal organic framework material, and natural wood to be carbonized; the carbonization method includes any one of tubular furnace heating, microwave heating, and laser heating.

9. The atomic-level catalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The atomic-level catalyst includes any one of a single-atom catalyst, a diatomic catalyst, a single-atom alloy catalyst, a diatomic alloy catalyst, and an atomic cluster catalyst.

10. Use of the atomic-level catalyst according to claim 9 in a catalytic reaction; The applications include applications in hydrogen production, oxygen production, industrial organic energy production, energy conversion, medical treatment, agriculture or environmental protection.

Citation Information

Patent Citations

  • Monatomic catalyst as well as preparation method and application thereof

    CN112221528A

  • Monatomic catalyst and preparation method and application thereof

    CN113430540A

  • Method for preparing metal single atoms through laser ablation

    CN114029505A

  • Metal monatomic catalyst and preparation method thereof

    CN111420691A

  • Method for in-situ preparation of ultra-small precious metal and non-precious metal alloy on carbon carrier

    CN114734051A

Cited By

  • Laser solid-phase in-situ constructed integrated membrane electrode and preparation method thereof

    CN121161329A